The Time Needed for Clinical Documentation versus Direct Patient Care - Ammenwerth, E.; Spötl, H.-P. (Methods of Information in Medicine, 2009)
Objectives: Health care professionals seem to be confronted with an increasing need for high-quality, timely, patient-oriented documentation. However, a steady increase in documentation tasks has been shown to be associated with increased time pressure and low physician job satisfaction. Our objective was to examine the time physicians spend on clinical and administrative documentation tasks. We analyzed the time needed for clinical and administrative documentation, and compared it to other tasks, such as direct patient care.Methods: During a 2-month period (December 2006 to January 2007) a trained investigator completed 40 hours of 2-minute work-sampling analysis from eight participating physicians on two internal medicine wards of a 200-bed hospital in Austria. A 37-item classifica tion system was applied to categorize tasks into five categories (direct patient care, communication, clinical documentation, administrative documentation, other).Results: From the 5555 observation points, physicians spent 26.6% of their daily working time for documentation tasks, 27.5% for direct patient care, 36.2% for communication tasks, and 9.7% for other tasks. The documentation that is typically seen as administrative takes only approx. 16% of the total documentation time.Conclusions: Nearly as much time is being spent for documentation as is spent on direct patient care. Computer-based tools and, in some areas, documentation assistants may help to reduce the clinical and administrative documentation efforts.
Keywords: Documentation; time and motion studies; workload; physicians; medical record systems